Changes in Severe Acute Respiratory Syndrome Coronavirus 2 Seroprevalence Over Time in 10 Sites in the United States, March–August, 2020. (26th February 2021) - Lim, Travis; Delorey, Mark; Bestul, Nicolette; Johannson, Michael A; Reed, Carrie; Hall, Aron J; Fry, Alicia M; Edens, Chris; Semenova, Vera; Li, Han; Browning, Peter; Desai, Rita; et al.
Abstract: Background: Monitoring of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibody prevalence can complement case reporting to inform more accurate estimates of SARS-CoV-2 infection burden, but few studies have undertaken repeated sampling over time on a broad geographic scale. Methods: We performed serologic testing on a convenience sample of residual serum obtained from persons of all ages, at 10 sites in the United States from 23 March through 14 August 2020, from routine clinical testing at commercial laboratories. We standardized our seroprevalence rates by age and sex, using census population projections and adjusted for laboratory assay performance. Confidence intervals were generated with a 2-stage bootstrap. We used bayesian modeling to test whether seroprevalence changes over time were statistically significant. Results: Seroprevalence remained below 10% at all sites except New York and Florida, where it reached 23.2% and 13.3%, respectively. Statistically significant increases in seroprevalence followed peaks in reported cases in New York, South Florida, Utah, Missouri, and Louisiana. In the absence of such peaks, some significant decreases were observed over time in New York, Missouri, Utah, and Western Washington. The estimated cumulative number of infections with detectable antibody response continued to exceed reported cases in all sites. Conclusions: Estimated seroprevalence was low in most sites, indicating that most people in the United States had not been infected with SARS-CoV-2 as of July 2020. The majority of infections are likely not reported. Decreases in seroprevalence may be related to changes in healthcare-seeking behavior, or evidence of waning of detectable anti–SARS-CoV-2 antibody levels at the population level. Thus, seroprevalence estimates may underestimate the cumulative incidence of infection. Abstract : The majority of people in the United States have not been infected with severe acute respiratory syndrome coronavirus 2. Reported cases continue to be less than estimated infections. Some statistically significant increases in seroprevalence followed spikes in reported cases. Some statistically significant decreases may be indirect evidence of waning of detectable antibodies at the population level.